Home and Hearth : An Archaeological Perspective on Acadian Domestic Architecture - Crépeau, Andrée; Christianson, David (Ethnologies, 1995)
During the last two decades a number of archaeologists have examined the remains of pre-1755 Acadian settlements. The authors review the findings of these excavations and surveys and discuss how the archaeological record reflects the surviving historical descriptions of Acadian houses. Patterns of house size, shape, structural elements and location are discussed.